Relationship between the skills of Critical and Creative Thinking and Autonomous Learning in students of the Faculty of Mathematical Sciences - Peña Miranda, Carlos Alberto (2018)
The objective of this research was to determine if critical and creative thinking and learning strategies are related to each other in a sample of students from the four schools that make up the Mathematical Sciences Faculty of the National University of San Marcos. A correlational descriptive design was used with a sample of 300 students to whom two evaluation instruments were applied: the inventory of critical and creative thinking of Alberto Acevedo and Marcela Carrera and the independent learning inventory of Manuel Torres. These instruments were subjected to the corresponding statistical analyzes that determined that the tests are valid and reliable. The results indicate that there are signicant and positive correlations between critical and creative thinking and autonomous learning (r = 0.80) among the students in the sample.